IMPROVING STUDENTS’ SELF CONFIDENCE IN SPEAKING ENGLISH SKILL BY USING DRAMA - Weny Noviany Rahayu (Journal of English Education Program (JEEP), 2017)
This paper deals with the investigating students’ self-confidence in speaking English skill by using drama. This study was aimed at investigating whether the use of drama could improve students’ self-confidence or not and the students’ perception about their self confidence in English speaking skill by using drama. The writer use a case study design as a research design of the study in order to gained the detail information how drama improve the students’ self-confidence in speaking. The population in this study all students at the third grade of English Departement in Galuh University. The sample of this study was one class of the third grade students as a sample of the study. In determining the sample, the writer used purposive sampling technique. The instruments used in this study consisted of two instruments including classroom observation and questionnaire. The results of data analysis showed that regarding the first research question, most of the students’ performance indicated have optimal self-confidence. Meanwhile, the diffident self-confidence was indicated in the conversation of drama. The last, the over self confidence also found on the students’ performance in performing the drama. The result also showed that there were some requirements of speaking which influence toward the students’ speaking performance. All those requiremets include the use of appropriate grammar, vocabularies, and spelling the appropriate pronunciation. All the requirements should be noticed by each of the speakers. In conclusions, the use of drama in speaking effective in improving students’ sel-confidence.